Austerity and distributional policy - Matteo Alpino; Zareh Asatryan; Sebastian Blesse; Nils Wehrhöfer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
What are the effects of austerity on distributional policy? We exploit the autonomy of Italian municipalities in setting non-linear income taxes and the exogenous introduction of a fiscal rule to show that austerity increases income tax progressivity. Consistent with this evidence, we find that in a panel of countries austerity correlates with higher marginal tax rates on top- but not on average-earners. The increase in progressivity in Italy is driven by high-skilled mayors, while low-skilled mayors raise taxes uniformly. In the election after the reform, high-skill mayors have higher reelection odds than low-skill mayors, while there was no difference beforehand.
Keywords: D78; H24; H70; 330; austerity; fiscal rules; non-linear income taxation; difference-in-discontinuity